Development over time in cognitive function among European 55-69-year-olds from 2006 to 2015, and differences of region, gender, and education - Ying Zhou (Comparative Population Studies (CPoS), 2022)
With populations rapidly aging, the development over time in the cognitive function among the elderly approaching or reaching retirement is important for successful aging at work and planning pension policies. However, few studies in this field focus on this age group. This study characterizes time trends in cognitive function among 55-69-year-old Europeans from 2006 to 2015, and compares these trends by region, gender, and education. This study analyzes 40,689 subjects in Waves 2, 4, 5 and 6 of the Survey of Health, Aging and Retirement in Europe (SHARE) covering ten countries. Cognitive function was measured by Recall and Verbal Fluency. Educational levels were classified by quartiles. A Generalized Estimating Equation (GEE) model was used to explore the association between cognitive function and development over time after controlling for confounders. Further stratification analysis using GEE models was conducted, stratified by region, gender and education. Cognitive function improved significantly in southern and central Europe over the observed timeframe, whereas it did not in northern Europe. Those with relative low levels of formal education displayed the most rapid increases in cognitive function in southern and central Europe. Among those with lower education in southern Europe, males' cognitive function improved more quickly than females'. The improvement of cognitive function at ages 55-69 in southern and central Europe may contribute to continuing engagement with productive activities in old age. Educational interventions for people with lower levels of education may be most effective in achieving such engagement. This paper extends the literature on the development over time in the cognitive function among the elderly close to retirement age in Europe by analysing southern, central and northern Europe, as well as differences by region, gender and education. The results may provide evidence for planning pension policies and educational interventions.
urn:nbn:de:bib-cpos-2022-04en0
Keywords: 300; Aging; Cognitive function; Education; Flynn effect